2018
DOI: 10.4028/www.scientific.net/msf.914.160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Borax on Properties of Potassium Magnesium Phosphate Cement

Abstract: The effects of borax on the setting time, compressive strength, bond strength, drying shrinkage and pH value were investigated for potassium magnesium phosphate cement (MKPC). The results show that with the increase of borax dosage, the setting time is gradually extended, both compressive strength and bond strength are greatly decreased, the drying shrinkage rate is increased. Especially high dosage of borax, the extension of setting time is more obvious. Compared with that without borax, when the dosage of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The reached final setting times are longer than those ones measured by Li et al [ 30 ], who manufactured samples with 5% and 10% of borax (mass percentage of the used MgO) that provided the final setting time 15 min and 25 min, respectively. The obtained results are also more promising than the initial setting times obtained by Wen et al [ 39 ], who measured initial setting times around 2 min, 2.5 min, 2.5 min, and 3.5 min for 2.5%, 5%, 7.5%, and 10% of borax, respectively. However, it should be taken into account that the used amount of borax in the mentioned experiments was slightly lower, as it was set as the mass percentage of MgO, while in this experiment, the borax share was calculated as the mass percentage of MgO + KH 2 PO 4 .…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The reached final setting times are longer than those ones measured by Li et al [ 30 ], who manufactured samples with 5% and 10% of borax (mass percentage of the used MgO) that provided the final setting time 15 min and 25 min, respectively. The obtained results are also more promising than the initial setting times obtained by Wen et al [ 39 ], who measured initial setting times around 2 min, 2.5 min, 2.5 min, and 3.5 min for 2.5%, 5%, 7.5%, and 10% of borax, respectively. However, it should be taken into account that the used amount of borax in the mentioned experiments was slightly lower, as it was set as the mass percentage of MgO, while in this experiment, the borax share was calculated as the mass percentage of MgO + KH 2 PO 4 .…”
Section: Resultssupporting
confidence: 69%
“…Of the mentioned examples, boron compounds are likely the most often used ones, as the retardation effect and impact on strength provided by the other possibilities is more complex and not always positive [ 17 , 34 ]. Among boron compounds, borax [ 17 , 26 , 30 , 31 , 37 , 38 , 39 ] and boric acid [ 35 , 40 , 41 ] are usually the used ones, both providing similar retarding effect when used in MPC-based composites [ 34 ]. The aforementioned reports indicate that the use of borax and its dosage significantly affects various material properties, some in a good way and some in an unwanted way.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, considering the main factors of the early properties of MPC, the mass ratio of magnesia-to-phosphate ( x 1 : M/P), the mass ratio of borax to magnesia ( x 2 : B/M) and the mass ratio of water to binder ( x 3 : W/b) are selected as the input factors of the optimization model. Some scholars have investigated the property of MPC under different mixing ratios and found that when the M/P falls within the range of 3–4 [ 19 , 37 ], the B/M is approximately 12.5% [ 38 , 39 ], and the W/b varies from 0.14 to 0.2 [ 40 , 41 ], the individual properties of MPC are closely with the requirements for the slab track repair. Consequently, this study broadens the range of each factor, setting the ranges for M/P, B/M, and W/b as 2.7 to 4.3, 0.11 to 0.17, and 0.12 to 0.22, respectively, to ensure that the factor ranges cover the various property aspects of MPC.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 6 shows the flexural strength of MKPC at different ages, when M:P is the same, the flexural strength shows a decreasing trend with the increase of FA doping. When the amount of FA and SF is the same, the larger the M:P is, the smaller the flexural strength is, and its early strength is influenced by M:P, and the specimen at 28 d age is less influenced by M:P. The main reason is that a certain amount of silica fume can give full play to the micro-aggregate filling effect and improve the particle gradation of MKPC mortar, while the silica fume particles can be used as nuclei to promote the development of hydration of potassium magnesium phosphate cement, which is beneficial to the development of flexural strength of potassium magnesium phosphate cement with the growth of age [32].…”
Section: Effect Of Flexural Strengthmentioning
confidence: 99%